A Case Study of Using Assisted Reproductive Technology to Rescue Genetically Modified Mice with Reproductive Disorder Phenotypes - WANG Qianqian; TAO Sijue; WEI Zhen; JIN Huihui; LIU Ping; WANG Lie (Shiyan dongwu yu bijiao yixue)
ObjectiveThe utilization of assisted reproductive technology to rescue genetically modified mouse strains with reproductive disorders provides a reference for improving techniques to preserve valuable experimental mouse strains.MethodsIn vitro fertilization-embryo transfer (IVF-ET) technology was performed on 28 strains of infertile male mice aged 9-18 months. Several indicators such as sperm density and sperm motility in infertile male mice were assessed to select the most viable sperm for IVF-ET experiments. Fertility rate, abnormal egg rate, and birth rate were recorded after the birth of the pups. An optimized ovarian transplantation procedure was applied to 12 strains of infertile female mice aged 8-18 months. 6-week-old female mice with the same genetic background were selected as recipients. One intact ovary was removed from each recipient mouse, and the contralateral oviduct was ligated. An ovary from a donor mouse was isolated and transplanted orthotopically into the side where the ovary had been removed in the recipient mouse. Twenty-one days post-surgery, recipient mice were co-housed with 8-week-old wild type male mice of the same genetic background for breeding. Data such as the pregnancy rate and live birth rate of the recipients were recorded after the birth of the pups.ResultsIVF-ET successfully rescued 28 mouse strains, with the oldest male mice being 18 months old. The success rate of the first round of IVF-ET experiments was 89.29% (25/28). The average fertility rate of IVF in infertile male mice was (51.01±14.97)%, the abnormal egg rate was (9.03±5.28)%, and the birth rate of offspring mice was (18.60±7.03)%. 39 out of 40 ovarian transplant recipient mice survived, with a pregnancy rate of 33.33% (13/39) for ovarian transplant recipients, and a live birth rate of 17.95% (7/39). Four mouse strains were successfully rescued using optimized ovarian transplantation technology, with the oldest female mice being 18 months old. 8 strains were not rescued as they failed to produce offspring that survived to sexual maturity.ConclusionIVF-ET is an effective approach for rescuing mice with reproductive disorders caused by different reasons, especially for those beyond the optimal breeding age. Ovarian transplantation technology can also be used as an alternative for aged female mice. But its success rate is relatively lower than that of IVF-ET, and carries a higher experimental risk.